JERUSALEM: KOTA DALAM SENGKETA - Sudrajat, Ajat (Jurnal Sejarah dan Budaya, 2009)
Abstract: This research is itended to trace the roots of conflict causes at city of Jerrusalem. The four steps taken of this research method are heuristic, source critique, interpretation and historiography. The findings of this research are (1) in fact, Jerusalem is a city always involved in conflict. There are several nations that have involved conflicts at this city, namely The Kanâan, Philistine, Jew, Babylonian, Asyyrian, Persia, Greece, Roman, Arabian-Islamic, and Roman-Christian; (2) In the contemporary era, Jerussalem is still the source of conflict between Palestine (Islam) and Jew; (3) The United Nations Organization declares that Jerrusalem is in international under control as corpus separatum.